2003
DOI: 10.1083/jcb.200302138
|View full text |Cite
|
Sign up to set email alerts
|

HIV Gag mimics the Tsg101-recruiting activity of the human Hrs protein

Abstract: The HIV-1 Gag protein recruits the cellular factor Tsg101 to facilitate the final stages of virus budding. A conserved P(S/T)AP tetrapeptide motif within Gag (the “late domain”) binds directly to the NH2-terminal ubiquitin E2 variant (UEV) domain of Tsg101. In the cell, Tsg101 is required for biogenesis of vesicles that bud into the lumen of late endosomal compartments called multivesicular bodies (MVBs). However, the mechanism by which Tsg101 is recruited from the cytoplasm onto the endosomal membrane has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
262
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(278 citation statements)
references
References 68 publications
15
262
1
Order By: Relevance
“…For comparison with previous measurements of fully formed virions, we examined the largest 10% of clusters, and found an average diameter of 166 +/-26 nm for Gag-mEos2 and 302 +/-90 nm for Gag-tdEos. For Gag-mEos2 this is in good agreement with EM of budded VLPs, reported in different studies to be 100-200 nm or 145 +/-25 nm in size 5,19 . It moreover indicates that the GagtdEos particles are unusually large.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…For comparison with previous measurements of fully formed virions, we examined the largest 10% of clusters, and found an average diameter of 166 +/-26 nm for Gag-mEos2 and 302 +/-90 nm for Gag-tdEos. For Gag-mEos2 this is in good agreement with EM of budded VLPs, reported in different studies to be 100-200 nm or 145 +/-25 nm in size 5,19 . It moreover indicates that the GagtdEos particles are unusually large.…”
supporting
confidence: 90%
“…In support of this, we estimate based on our measurements of nascent virion size and protein number that the Gag-tdEos forms a patchy lattice covering only ~10-20% of the virion surface, based on the lattice spacing measured by EM. As further evidence, a separate study of elongated Gag proteins revealed an increase in virion size and a discontinuous density of Gag 19 . However, our data allow us to go further, in showing that these differences in packing exist throughout most of the assembly process.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Gag drives HIV-1 budding through the Gag p6 late domain (L domain). L domain binds the tumour susceptibility gene 101 (TSG101), hijacking the host's MVB vesicle formation machinery, and recruits proteins of the ESCRT (endosomal sorting complexes required for transport) family, which regulate MVB biogenesis and cellular vacuolar protein sorting pathways (Pornillos et al, 2003;Strack et al, 2003;von Schwedler et al, 2003). The release of HIV-1 also seems to differ in T cells and in macrophages.…”
Section: Virus Assembly and Releasementioning
confidence: 99%
“…In addition to Vps28, a component of yeast and mammalian ESCRT-I (Katzmann et al 2001;Martin-Serrano et al 2003), an as-yet-unidentified mammalian ortholog of yeast Vps37 likely complements the action of Tsg101. Recent reports identified two additional partners of Tsg101, namely, AIP1, the ortholog of Bro1 (Strack et al 2003;von Schwedler et al 2003), and Hrs (Bache et al 2003a;Katzmann et al 2003;Pornillos et al 2003). In an effort to resolve the sorting action of Tsg101, we screened cDNA libraries for Tsg101-associated proteins by using the yeast two-hybrid system.…”
mentioning
confidence: 99%